Association and histological characteristics of endplate injury and intervertebral disc degeneration in a rat model. Issue 8 (August 2021) - Su, Qihang; Li, Yongchao; Feng, Xiaofei; Tan, Jun; Ge, Hengan; Cheng, Biao; Zhang, Yan
Highlights: The association between endplate cartilage injury and adjacent disc degeneration has not been investigated in animal fracture models. The purpose of this study was to analyze the association and histological characteristics of endplate injury and disc degeneration in a rat model. The histological differences were detected using imaging, non-specific histological staining, immunohistochemistry and TUNEL assay. A fracture with endplate injury in rat caudal vertebral body fractures is a key to accelerate degeneration of adjacent intervertebral discs. Abstract: Introduction: The purpose of this study was to construct a rat caudal vertebral body fracture model and to analyze the association and histological characteristics of vertebral body fracture with endplate injury and adjacent intervertebral disc degeneration. Materials and methods: This study included 144 clean-grade male Sprague-Dawley rats, which were randomly divided into a control, middle vertebral body injury (MI), and endplate injury (EI) groups. A vertebral body fracture with or without endplate injury was developed by either drilling a hole in the middle of a rat caudal vertebral body to create a fracture with an intact endplate or drilling a hole in the vertebral body near the intervertebral disc to create a vertebral body fracture with endplate injury. The histological differences in the adjacent intervertebral discs of vertebral body fractures with or without endplate injury were detected using imaging, non-specific histological staining, immunohistochemistry and TUNEL assay. Results: Imaging results revealed that the EI group showed a significant decrease in intervertebral space height and intervertebral disc T2 signal over time. Non-specific histological staining revealed that in the EI group, the intervertebral disc was degenerative. Immunohistochemistry indicated that Aggrecan and Collagen-II were decreased and inflammatory factors were increased in the EI group. The TUNEL detection found that apoptosis was significantly increased in the EI group as compared with the MI and control groups. Conclusion: In rat caudal vertebral body fractures, a fracture with endplate injury is more likely to induce or accelerate degeneration of adjacent intervertebral discs.